Pathophysiology : concepts of altered health states - Porth, Carol Mattson; Kunert, Mary Pat (Philadelphia, Pennsylvania : Lippincott Williams & Wilkins, 2002)
Now celebrating its 20th anniversary, the Sixth Edition of this bestseller continues to offer an unparalleled presentation of the discipline of Pathophysiology. This edition includes the addition of three new chapters: "Concepts of Health and Disease," "Sleep and Sleep Disorders," and "Neurobiology of Thought and Mood Disorders." Essential information is provided, clarifying the interrelationships between normal body functioning to the physiologic changes that participate in disease production and occur as a result of disease, as well as the body's ability to compensate for these changes. Coverage is based on common health problems for all segments of the population, including the special needs of children and elderly persons. An abundance of learning tools--including in-text summaries, chapter outlines, learning objectives, key concept boxes, Internet addresses and extensive explanations--reinforce material and maximize learning potential. This full-color edition, now with seventy-five new illustrations as well as enhancements to existing illustrations, continues to provide visual appeal to facilitate the learning process.
Unit I Concepts of Health and Disease 1 (60) Concepts of Health and Disease 3 (18) Concepts of Altered Health in Children 21 (22) Concepts of Altered Health in Older Adults 43 (18) Unit II Cell Function and Growth 61 (118) Cell and Tissue Characteristics 63 (32) Cellular Adaptation, Injury, and Death and Wound Healing 95 (20) Genetic Control of Cell Function and Inheritance 115 (16) Genetic and Congenital Disorders 131 (18) Alterations in Cell Differentiation: Neoplasia 149 (30) Unit III Integrative Body Functions 179 (70) Stress and Adaptation 181 (14) Alterations in Temperature regulation 195 (14) Alterations in Nutritional Status 209 (22) Alterations in Activity Tolerance 231 (18) Unit IV Hematopoietic Function 249 (58) Blood Cells and the Hematopoietic System 251 (8) Alterations in Hemostasis 259 (12) The Red Blood Cell and Alterations in Oxygen Transport 271 (20) Disorders of White Blood Cells and Lymphoid Tissues 291 (16) Unit V Infection, Immunity, and Inflammation 307 (90) Mechanisms of Infectious Disease 309 (22) Immunity and Inflammation 331 (26) Alterations in the Immune Response 357 (22) Acquired Immunodeficiency Syndrome 379 (18) Unit VI Cardiovascular Function 397 (178) Control of the Circulation 399 (30) Alterations in Blood Flow in the Systemic Circulation 429 (30) Alterations in Blood Pressure: Hypertension and Orthostatic Hypotension 459 (28) Alterations in Cardiac Function 487 (44) Disorders of Cardiac Conduction and Rhythm 531 (16) Heart Failure and Circulatory Shock 547 (28) Unit VII Respiratory Function 575 (96) Control of Respiratory Function 577 (28) Alterations in Respiratory Function: Respiratory Tract Infections, Neoplasms, and Childhood Disorders 605 (28) Alterations in Respiration: Alterations in Ventilation and Gas Exchange 633 (38) Unit VIII Renal Function and Fluid and Electrolytes 671 (142) Control of Renal Function 673 (20) Alterations in Fluids and Electrolytes 693 (42) Alterations in Acid-Base Balance 735 (18) Alterations in Renal Function 753 (24) Renal Failure 777 (18) Alterations in Urine Elimination 795 (18) Unit IX Gastrointestinal Function 813 (76) Control of Gastrointestinal Function 815 (16) Alterations in Gastrointestinal Function 831 (28) Alterations in Function of the Hepatobiliary System and Exocrine Pancreas 859 (30) Unit X Endocrine Function 889 (64) Mechanisms of Endocrine Control 891 (12) Alterations in Endocrine Control of Growth and Metabolism 903 (22) Diabetes Mellitus 925 (28) Unit XI Genitourinary and Reproductive Function 953 (88) Structure and Function of the Male Reproductive System 955 (10) Alterations in Structure and Function of the Male Genitourinary System 965 (18) Structure and Function of the Female Reproductive System 983 (14) Alterations in Structure and Function of the Female Reproductive System 997 (32) Sexually Transmitted Diseases 1029 (12) Unit XII Neural Function 1041 (194) Organization and Control of Neural Function 1043 (48) Somatosensory Function and Pain 1091 (32) Alterations in Motor Function 1123 (36) Disorders of Brain Function 1159 (42) Sleep and Sleep Disorders 1201 (18) Neurobiology of Thought, Mood, and Anxiety Disorders 1219 (16) Unit XIII Special Senses 1235 (74) Control of Special Senses 1237 (26) Alterations in Vision 1263 (28) Alterations in Hearing and Vestibular Function 1291 (18) Unit XIV Musculoskeletal Function 1309 (82) Structure and Function of the Skeletal System 1311 (10) Alterations in Skeletal Function: Trauma and Infection 1321 (20) Alterations in Skeletal Function: Congenital Disorders, Metabolic Bone disease, and Neoplasms 1341 (26) Alterations in Skeletal Function: Rheumatic Disorders 1367 (24) Unit XV Integumentary Function 1391 (54) Control of Integumentary Function 1393 (8) Alterations in Skin Function and Integrity 1401 (44) Appendix 1445 (2) Glossary 1447 (10) Index 1457
Includes bibliographical references and index.
Keywords: PHYSIOLOGY, PATHOLOGICAL